La idea de criminalidad y castigo en Morelia durante el porfiriato - Guevara Sánchez, Berenice (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
The ideas represent us, and in a historical context they are a window to the forms of understanding the world. In this work we are about analyzing how he/she understood each other to the transgressor of crimes against the life - homicide and wounded -, which were considered as crimes against people and they represented for the society a serious transgression, because he/she implied making use of the violence against a person. The actors could be reduced to two terms: "criminal" and "criminal." The revised crimes were carried out in the city of Morelia, and they were processed by the first penal tribunal of the city. The city allowed us the understanding of particular realities, but that he/she also resembled each other with what happened in other parts of the country. He/she is in charge of the investigation of the punishment administered by the modern State on the homicide or heridor.1 are developed the analysis in two perspectives: a, anchored in the application and perception of the punishment, and another in the society that imagines the transgressor like "criminal" or "criminal" and that it sanctions it with the rejection and the exclusion that are translated in stigma. More than a history of the punitive ideas, or of the prison institutions, this work is in charge of of reconstructing the forms in that the society moreliana perceived the homicide criminal and wounded. Ideas that have been embroidered throughout the history with base in trials moral, long debates that have involved different actors like the Church and the State. In turn the "science" has been made voice to define to the "other" one either understanding this as a being different to the common one for birth or for apprehended behavior.

Las ideas nos representan, y en un contexto histórico son una ventana a las formas de entender el mundo. En este trabajo tratamos de analizar cómo se entendía al transgresor de delitos contra la vida -homicidio y heridas-, los cuales se consideraban como delitos contra las personas y representaban para la sociedad una grave transgresión, pues implicaba el hacer uso de la violencia en contra de una persona. Los actores podían ser reducidos a dos términos: “criminal” y “delincuente”. Los delitos revisados fueron realizados en la ciudad de Morelia, y fueron procesados por el primer juzgado penal de la ciudad. La ciudad nos permitió la comprensión de realidades particulares, pero que también se asemejaba con lo que sucedía en otras partes del país. Se ocupa la investigación del castigo administrado por el Estado moderno sobre el homicida o heridor.1 Se desarrolla el análisis en dos perspectivas: una, anclada en la aplicación y percepción del castigo, y otra en la sociedad que imagina al transgresor como “delincuente” o “criminal” y que lo sanciona con el rechazo y la exclusión, que se traducen en estigma. Más que una historia de las ideas punitivas, o de las instituciones carcelarias, este trabajo se ocupa de reconstruir las formas en que la sociedad moreliana percibió al delincuente de homicidio y heridas. Ideas que se han bordado a lo largo de la historia con base en juicios morales, largos debates que han involucrado diferentes actores como la Iglesia y el Estado. A su vez la “ciencia” se ha hecho voz para definir al “otro” entendiendo a éste como un ser diferente al común ya sea por nacimiento o por conducta aprehendida.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2008-0009; Opción en historia de México; Criminalidad; Castigo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2377